OTORITAS TUHAN DI TANGAN BIROKRASI: Menimbang Batas Intervensi Negara terhadap Syariah Menurut Yudian Wahyudi dan Abdullahi Ahmed An-Na’im - David, Mohammad; Habim, Nurdin; Sadari, Sadari (Asosiasi Dosen PTKIS Indonesia, 2026)
This article examines Human Rights (HAM) and Equality in Sharia according to Yudian Wahyudi and Abdullahi Ahmed An-Na’im. According to an-Na’im, human rights are universal as a minimum ethical standard that must be met by all legal systems, including Islamic law. Sharia must be reformed so as not to conflict with the principles of gender equality, religious freedom, and non-discrimination. An-Na’im does not hesitate to directly criticize classical Islamic legal texts. Meanwhile, Yudian presents a style of Islamic legal approach that is sourced from the Islamic treasure, namely ushul fiqh, not hermeneutics. According to him, maqasid sharia is actually the correct method in the exploration (al-istinbati) and application (at-tabiqi) of Islamic law. Thus, the difference between Yudian and an-Na’im lies in the level of methodological radicalism and the basis of normative legitimacy. Yudian tends to maintain continuity with the tradition of ushul fiqh and the authority of texts, while an-Na’im is more daring in deconstructing the normative structure of classical sharia. However, the two agreed that formalizing sharia as state law was not an ideal solution to the problems of modern Muslims. Yudian maintained continuity with the traditions of ushul fiqh and the authority of texts. His thinking style was characterized by continuity (istimrar), change (taghayyur), and transcendence (muta’alin), complemented by comparison and contrast. He pursued the maqasid of sharia in Yudian's style, using maqasid sharia as a method. Theoretically, the synthesis of Yudian's and an-Na’im's thinking opens the opportunity for a more comprehensive model of Islamic legal reform. From Yudian, we can draw a contextual maqasid sharia approach that is sensitive to local realities. From an-Na’im, we can draw a strong commitment to equality, freedom, and human dignity as universal ethical principles. This synthesis does not eliminate differences, but rather leverages the strengths of each approach to more comprehensively address legal and humanitarian challenges.